2018
DOI: 10.1159/000490170
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Cholesterol Reduces ENaC Activity by Decreasing Phosphatidylinositol-4,5-Bisphosphate in Microvilli

Abstract: Background/Aims: The epithelial sodium channel (ENaC) in cortical collecting duct (CCD) principal cells plays a critical role in regulating systemic blood pressure. We have previously shown that cholesterol (Cho) in the apical cell membrane regulates ENaC; however, the underlying mechanism remains unclear. Methods: Patch-clamp technique and confocal microscopy were used to evaluate ENaC activity and density. Results: Here we show that extraction of membrane Cho with methyl-β-cyclodextrin (MβCD) significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…We have shown that pharmacological blockade of ABCA1 with CsA elevates intracellular cholesterol, increases ENaC activity, and induces hypertension (Wang et al, ; Zhai et al, , https://doi.org/10.1016/j.bbadis.2018.08.027). To further determine the role of ABCA1, ABCA1 flox mice were crossed with AQP‐2 Cre mice to selectively delete ABCA1 in CCD principal cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that pharmacological blockade of ABCA1 with CsA elevates intracellular cholesterol, increases ENaC activity, and induces hypertension (Wang et al, ; Zhai et al, , https://doi.org/10.1016/j.bbadis.2018.08.027). To further determine the role of ABCA1, ABCA1 flox mice were crossed with AQP‐2 Cre mice to selectively delete ABCA1 in CCD principal cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, loss of the cilium‐controlled ATP release should account for the increased ENaC P O in ABCA1 KO mice. Using a cell culture model, our recent studies have already shown that depletion of cholesterol by lovastatin reduces ENaC activity by decreasing PIP 2 in microvilli in cultured distal nephron cells (Zhai et al, ). These studies suggest that principal cells have a mechanism by which they control sodium reabsorption that depends upon distal nephron flow, the primary cilia, and ATP release from the cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations